Do Investments in Clean Technologies Reduce Production Costs? Insights from the Literature - Timilsina, Govinda (World Bank, Washington, DC, 2021)
In response to growing environmental concerns, particularly climate change, governments have encouraged innovation and adoption of clean technologies through various policy measures. At present more than half a trillion US dollars is being invested annually in clean technologies. Based on the existing literature, this study analyzes whether investments in clean technologies increase productivity. The findings are mixed. Employing firm-level data, the majority of ex-post studies show a positive relationship between clean investments and firms’ productivity, especially in the energy-intensive manufacturing sector. Most studies for the transport, building and power sector use an ex-ante, technology or sectoral level analysis instead of ex-post analysis to examine the economics of clean technologies. In the transport sector, transportation services with electricity or hydrogen are still more expensive than that with gasoline and diesel vehicles. Some studies, however, project that cleaner vehicles will be economically attractive within a decade. Many studies report that clean technologies reduce energy consumption and save energy bills in the building sector, although some studies do not agree. Most studies for the power sector indicate that renewable technologies have not yet reduced the average costs of grid electricity because of their intermittency and a smaller share in the total electricity supply.